2017
DOI: 10.1155/2017/8242313
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Lassa Fever Disease in Northern Togo: Report of Two Cases in Oti District in 2016

Abstract: Background Lassa fever belongs to the group of potentially fatal hemorrhagic fevers, never reported in Togo. The aim of this paper is to report the first two cases of Lassa fever infection in Togo. Case Presentation The two first Lassa fever cases occurred in two expatriate's health professionals working in Togo for more than two years. The symptoms appeared among two health professionals of a clinic located in Oti district in the north of the country. The absence of clinical improvement after antimalarial tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 16 publications
(23 reference statements)
1
19
0
Order By: Relevance
“…reported that the outbreak of LHF was due to the poor living conditions of the community [23]. This result goes in the same direction as ours.…”
Section: Discussionsupporting
confidence: 87%
“…reported that the outbreak of LHF was due to the poor living conditions of the community [23]. This result goes in the same direction as ours.…”
Section: Discussionsupporting
confidence: 87%
“…Recently, however, two new LASV lineages emerged in Mali, Cô te d'Ivoire, Benin, and Togo (Manning et al, 2015;Whitmer et al, 2018). These lineages, termed LV and LVI, were linked to demonstrated humanto-human transmission and death in Germany and in Africa (Manning et al, 2015;McElroy et al, 2017;Patassi et al, 2017;Whitmer et al, 2018). A 2015-2016 surge in Nigeria was associated with 60% case fatality in clinic (Buba et al, 2018;Roberts, 2018;Tambo et al, 2018), with an unprecedented and more geographically disperse surge occurring in 2017-2018 (Roberts, 2018;Tambo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…First identified in 1969 in Nigeria,11 Lassa fever is now endemic in West Africa including Nigeria, Sierra Leone, Guinea, Liberia, Benin, Ghana and Mali and has spread to neighbouring countries (figure 1). 12–15 In some areas, 10%–16% of people admitted to hospitals every year have LASV 1. Cases have also been identified in Germany,13 15 16 the Netherlands,17 18 Sweden,19 the USA,20–22 the UK23 24 and Japan,25 largely imported after travel in West Africa 17 26–28.…”
Section: Introductionmentioning
confidence: 99%